2015
DOI: 10.1016/j.celrep.2015.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Direct Visualization of HIV-1 Replication Intermediates Shows that Capsid and CPSF6 Modulate HIV-1 Intra-nuclear Invasion and Integration

Abstract: Summary Direct visualization of HIV-1 replication would improve our understanding of the viral lifecycle. We adapted established technology and reagents to develop an imaging approach, ViewHIV, which allows evaluation of early HIV-1 replication intermediates, from reverse transcription to integration. These methods permit the simultaneous evaluation of both the capsid protein (CA) and viral DNA genome (vDNA) components of HIV-1 in both the cytosol and nuclei of single cells. ViewHIV is relatively rapid, uses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
204
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(241 citation statements)
references
References 37 publications
(65 reference statements)
25
204
2
Order By: Relevance
“…The decreased colocalization of EdU and CA that we observed in MDM cultured with SIV-VLP may be a consequence of accelerated reverse transcription due to increased dNTP pools and thus a faster uncoating of the RTCs. These data demonstrating the association of HIV-1 DNA and CA in the nucleus of HIV-1-infected MDM are consistent with results from previous studies (13,15) and further validate the model that capsid fragments assist the HIV RTC in entering the nucleus during primary cell infection.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The decreased colocalization of EdU and CA that we observed in MDM cultured with SIV-VLP may be a consequence of accelerated reverse transcription due to increased dNTP pools and thus a faster uncoating of the RTCs. These data demonstrating the association of HIV-1 DNA and CA in the nucleus of HIV-1-infected MDM are consistent with results from previous studies (13,15) and further validate the model that capsid fragments assist the HIV RTC in entering the nucleus during primary cell infection.…”
Section: Resultssupporting
confidence: 80%
“…Interestingly, in addition to modulating uncoating and RT, the interaction of CA with host proteins can dictate the nuclear import pathway and integration site selection, suggesting that CA may play a role in the nucleus of infected cells (9)(10)(11)(12). Support for this finding has been observed in several recent imaging studies in which CA was shown to be associated with HIV-1 in the nuclei of infected cells (13)(14)(15).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…It also will be of interest to more precisely locate this block to infection, which might occur during uncoating, docking at the nuclear envelope, or nuclear entry itself. Future experiments to address this issue could include measures of viral uncoating, such as CsA-washout (90), fate-of-capsid (91), or imaging assays (reviewed in reference 19) or visualization of the infectious RTC/PIC (30,92). In contrast to overexpression, we found that silencing SUN2 in cell lines did not change the percentage of HIV-infected cells, although experiments in other cell types, including primary cells, could provide clarification.…”
Section: Discussionmentioning
confidence: 47%
“…CPSF6 and CypA binding to CA may also limit innate immune recognition of HIV (29). Nuclear (fulllength) CPSF6 also mediates the depth of nuclear entry of the preintegration complex (PIC) (30). The importance of nuclear topology for integration into active transcriptional units was underscored by recent findings that nucleoporin-mediated entry of the PIC into the nucleus, and provirus integration into the nuclear periphery, are intimately linked (31,32).…”
mentioning
confidence: 92%